The Influence of Predict, Observe, and Explain (POE) Learning Accompanied by Formative Assessment of Misconceptions and Mastery of Students’ Concepts of Temperature and Heat Material - Ilmar, Ahmad; Kusairi, Sentot; Khusaini, Khusaini (Jurnal Pendidikan Sains, 2023)
High misconceptions and students' mastery of concepts that are low enough are detected in temperature and heat material. To overcome this, teachers must apply learning strategies that are able to actively involve students in observation activities, namely the POE learning strategy. However, POE learning is not always easy to apply, students are still weak in communicating the results of their experiments. Therefore, a way is needed that helps students during the learning process to be more confident and not afraid when asked to argue, namely with formative assessment. POE learning accompanied by formative assessment aims to enable students to understand physics concepts by providing students with an active role during the teaching and learning process. This study aims to determine the influence of POE learning accompanied by formative assessment on misconceptions and mastery of student concepts on temperature and heat material. This research method is Quasi-Experiment. The research sample consisted of 94 grade XI students from one of the schools in South Sulawesi who were divided into one experimental class and two control classes. This study uses two types of instrument questions, namely four tier tests to obtain misconception data and evaluation tests for concept mastery data. Based on the results of data analysis, it is known that there is a significant difference in the average score of misconceptions between the experimental class and the control class. The average score of misconceptions in the experimental class was 14.53%, in control class 1 it was 22.19% and in control class 2 it was 30.17%. The average value of mastery of concepts was 81.88% for the experimental class, 75.62% for the control class and 68.17% for the control class 2. POE learning strategies accompanied by formative assessments have proven effective in correcting misconceptions and mastery of student concepts on temperature and heat material. DOI: https://doi.org/10.17977/jps.v11i42023p151